2016
DOI: 10.1667/rr14417.1
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cells and DNA Damage Response to Ionizing Radiations

Abstract: Pluripotent stem cells (PSCs) hold great promise in regenerative medicine, disease modeling, functional genomics, toxicological studies and cell-based therapeutics due to their unique characteristics of self-renewal and pluripotency. Novel methods for generation of pluripotent stem cells and their differentiation to the specialized cell types such as neuronal cells, myocardial cells, hepatocytes, and beta cells of the pancreas and many other cells of the body are constantly being refined. Pluripotent stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 112 publications
1
5
0
Order By: Relevance
“…Similar results were obtained in human ES cells and hiPSCs when exposed to girradiation, resulting in capase-3 cleavage within four hours of treatment [10]. Interestingly, PSCs exhibit a response to DNA damage that is remarkably similar regardless of lineage, whereas the DNA damage response elicited by differentiated somatic cells is highly cell-type dependent [11]. Recent data also demonstrated that the degree of pluripotency contributes to the DNA damage response elicited by irradiation, with iPSCs exhibiting a greater response than neonatal stromal cells, both of which are more sensitive than adult stromal cells [12].…”
Section: Introductionsupporting
confidence: 73%
“…Similar results were obtained in human ES cells and hiPSCs when exposed to girradiation, resulting in capase-3 cleavage within four hours of treatment [10]. Interestingly, PSCs exhibit a response to DNA damage that is remarkably similar regardless of lineage, whereas the DNA damage response elicited by differentiated somatic cells is highly cell-type dependent [11]. Recent data also demonstrated that the degree of pluripotency contributes to the DNA damage response elicited by irradiation, with iPSCs exhibiting a greater response than neonatal stromal cells, both of which are more sensitive than adult stromal cells [12].…”
Section: Introductionsupporting
confidence: 73%
“…When DNA damage cannot be repaired, cells undergo senescence, apoptosis or differentiation. The specific response triggered by genotoxic stress largely depends on the stem cell type and their developmental context ( Mujoo et al, 2016 ).…”
Section: Differential Responses To Dna Damage Depending On Cellular C...mentioning
confidence: 99%
“…Yet, our knowledge of DNA damage and repair responses to radiation comes predominantly from somatic cell models. Although human stem cells have been studied for their DNA damage and repair responses to acute radiation exposures [ 22 24 ], very few studies have used prolonged irradiation [ 25 ]. Multipotent mesenchymal stem cells (MSCs) are a well-characterized type of stem cells [ 26 ], widely used in stem cell-based therapy of various diseases [ 26 ].…”
Section: Introductionmentioning
confidence: 99%